Development and validation of an oral anticoagulation knowledge tool (AKT) - Obamiro, K.; Stafford, Leanne; Bereznicki, L. (Public Library of Science, 2016)
© 2016 Obamiro et al.This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.Background Assessing and improving patients' anticoagulation knowledge can lead to better treatment outcomes.While validated knowledge instruments exist for use in people taking warfarin, these tools are not necessarily applicable to patients taking direct-acting oral anticoagulants. Objective To develop and validate an oral anticoagulation knowledge instrument that is applicable to all oral anticoagulant medications. Methods Ten anticoagulation experts participated in the development of the Anticoagulation Knowledge Tool to ensure content validity. The knowledge instrument was administered to three groups of participants comprising of 44 pharmacists, 50 patients and 50 members of the general public. A subgroup of participants in the patient and pharmacist group were retested approximately 2-3 months after the initial testing. Statistical tests were conducted to determine the validity and reliability of the scale, and item analysis was used to determine the performance of individual questions. Results The 28-item instrument developed had a scale content validity index of 0.92, supporting content validity. The pharmacist group's mean score was significantly higher than that of the patient group, and the patient group scored significantly higher than the general public group (94% vs 62% vs 20%, respectively; p<0.001), supporting construct validity. Internal consistency reliability was acceptable with a Cronbach's a value of > 0.7 across the three groups, and the test-retest reliability was confirmed with a Pearson's correlation coefficient of 0.72 and 0.78 for the pharmacist and patient groups, respectively. Conclusion The Anticoagulation Knowledge Tool is a valid and reliable instrument that can be used in routine clinical practice to assess patients' anticoagulation knowledge.